Preparation and Antioxidant Activity Evaluation of Jerusalem Artichoke Polysaccharide-Zn Complex - Yashi ZHANG; Wenwen LI; Aizhen ZONG; Zhaohe ZUO; Zhenjia ZHENG; Bin ZHANG (Shipin gongye ke-ji, 2023)
Jerusalem artichoke polysaccharide (JAP)-Zn complex was prepared using JAP and ZnSO4 as raw materials, and single factor and response surface methodology methods were applied for the optimization preparation process of JAP-Zn complex. Besides, the antioxidant activities in vitro of JAP and JAP-Zn complex were investigated. The optimal preparation process of the JAP-Zn complex was as follows: The weight ratio of JAP and ZnSO4 was 32:1, the reaction time was 60 min, the reaction temperature was 50 °C, and the reaction pH was 8.50. Under these conditions, the chelation rate was 87.06%±0.28%. The results of antioxidant activity in vitro showed that both JAP and JAP-Zn complex exhibited excellent antioxidant activity in the concentration range of 0.3~2.7 mg/mL. The maximum scavenging capacity of JAP-Zn complex on the maximum scavenging rates of DPPH free radical, hydroxyl free radical and superoxide anion free radical, ABTS+ free radical was 23.42%, 13.47%, 29.36% and 18.50%, respectively. The results would provide a theoretical basis for the development of functional foods and nutritional supplements for JAP and JAP-Zn complex.